2016
DOI: 10.1038/ncomms12562
|View full text |Cite
|
Sign up to set email alerts
|

Single-point single-molecule FRAP distinguishes inner and outer nuclear membrane protein distribution

Abstract: The normal distribution of nuclear envelope transmembrane proteins (NETs) is disrupted in several human diseases. NETs are synthesized on the endoplasmic reticulum and then transported from the outer nuclear membrane (ONM) to the inner nuclear membrane (INM). Quantitative determination of the distribution of NETs on the ONM and INM is limited in available approaches, which moreover provide no information about translocation rates in the two membranes. Here we demonstrate a single-point single-molecule FRAP mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 32 publications
2
50
0
Order By: Relevance
“…Conventional subcellular fractionation and immunolocalization approaches have shown that some of these, including Myorg/Net37 [25] and Plpp7/Net39 [26], are enriched at the NE. New superresolution microscopy approaches are emerging [27] to evaluate whether such transmembrane proteins are concentrated at the NE relative to the peripheral ER ( de facto implying a distinctive nuclear function), or simply are ER residents that are not NE-excluded [28 • ]. …”
Section: The Regulatory Framework At the Inner Nuclear Membranementioning
confidence: 99%
“…Conventional subcellular fractionation and immunolocalization approaches have shown that some of these, including Myorg/Net37 [25] and Plpp7/Net39 [26], are enriched at the NE. New superresolution microscopy approaches are emerging [27] to evaluate whether such transmembrane proteins are concentrated at the NE relative to the peripheral ER ( de facto implying a distinctive nuclear function), or simply are ER residents that are not NE-excluded [28 • ]. …”
Section: The Regulatory Framework At the Inner Nuclear Membranementioning
confidence: 99%
“…By using the full width at half maximum (FWHM) as determined by data analysis software (a built-in function in Origin 6.1 is used here), the range between where points can lie along either side of the NE can be determined for further analysis such as diffusion coefficient and protein concentration along the NE (see Mudumbi et al 2016 for the relevant formulae).…”
Section: Basic Protocolmentioning
confidence: 99%
“…], including the lateral diffusion of NETs on the NE (Ellenberg et al, 1997) (25). Here we have further developed the FRAP technique by adapting a diffraction-limit photobleaching area and recording the recovery of single NETs on the INM and ONM with super-high spatiotemporal resolutions in live cells (Mudumbi et al, 2016). …”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…For their localization, SRM methods with an axial resolution of more than 10 nm have been developed [130, 131]. …”
Section: Nuclear Membranementioning
confidence: 99%